(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores modern methods and strategies for teaching synonyms, antonyms, and phraseological units in Russian as a Foreign Language (RFL). We highlight the significance of these linguistic elements in enhancing students’ vocabulary, cultural competence, and communicative skills. The study examines innovative approaches such as contextual learning, comparative analysis, and interactive techniques, emphasizing their role in fostering a deeper understanding of semantic relationships and idiomatic expressions. Furthermore, it discusses the application of digital tools and gamification in language instruction to improve engagement and retention. Practical recommendations and examples are provided to aid educators in effectively implementing these methods in their teaching practices.